Metode Penilaian Investasi dengan Analisis Sensitivitas Pada Pendirian UMKM “Premier Crepes” - Tuti Zakiyah (P4M STIE Putra Bangsa, 2018)
The main purpose of the investment is to earn a profit or a high rate of return. That is, no investor wants to lose even loss of funds or capital that has been invested in certain instruments. Well, to make no mistake in taking investment decisions, obligatory for investors to conduct investment feasibility analysis. Investment feasibility can not be judged solely on the basis of assumptions or beliefs, but must be analyzed in depth from various aspects. Without careful consideration, investing is like buying a cat in a sack. That is, investors do not know clearly whether the investment is profitable or not. Sensivitas analysis is an analysis conducted to determine the effect of changes in production parameters on changes in production system performance in generating profit. By conducting a sentiment analysis then the likely effect of these changes can be known and anticipated beforehand. An approach based on the Cash flow concept of Payback Period Method, Net Present Value (NPV) Method and Internal Rate of Return (IRR) Method. Minimum Acceptable Rate of Return or Minimum Atractive Rate of Return (MARR). MARR is the minimum rate of return on an investment that a brave investor would undertake.Keywords : NPV, IRR, MARR, sensitivity.